The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.drugalcdep.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Cessation of alcohol consumption decreases rate of nicotine metabolism in male alcohol-dependent smokers

Abstract: Background Rate of nicotine metabolism is an important factor influencing cigarette smoking behavior, dependence, and efficacy of nicotine replacement therapy. The current study examined the hypothesis that chronic alcohol abuse can accelerate the rate of nicotine metabolism. Nicotine metabolite ratio (NMR, a biomarker for rate of nicotine metabolism) and patterns of nicotine metabolites were assessed at three time points after alcohol cessation. Methods Participants were 22 Caucasian men randomly selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…To account for this difference, CYP2A6-k cat was estimated separately for the smoker subpopulation, leading to a lower k cat in comparison to the non-smoker subpopulation (see Table 1). [15,22,23]. Moreover, predicted bioavailabilities after oral (~ 35%) and pulmonary (~ 85%) administration of nicotine are in concordance with the literature (20-45% and 80-90%, respectively) [9,15,46].…”
Section: (B)supporting
confidence: 86%
See 1 more Smart Citation
“…To account for this difference, CYP2A6-k cat was estimated separately for the smoker subpopulation, leading to a lower k cat in comparison to the non-smoker subpopulation (see Table 1). [15,22,23]. Moreover, predicted bioavailabilities after oral (~ 35%) and pulmonary (~ 85%) administration of nicotine are in concordance with the literature (20-45% and 80-90%, respectively) [9,15,46].…”
Section: (B)supporting
confidence: 86%
“…Distribution and elimination processes including CYP enzymes and transporters were implemented according to the literature [ 15 , 21 23 ]. For the nicotine model, these are (1) metabolism of nicotine to its major metabolite cotinine through CYP2A6 and CYP2B6, (2) an unspecific hepatic clearance being responsible for the remaining hepatic metabolism of nicotine including metabolism via uridine 5ʹ-diphospho-glucuronosyltransferase 2B10 (UGT2B10) and flavin-containing monooxygenase 3 (FMO3), and (3) two transporters for the influx and efflux of nicotine across the blood–brain barrier (BBB).…”
Section: Methodsmentioning
confidence: 99%
“…However, an association between NMR and alcoholic drinks per month was not found in a mixed sample of smokers and non-smokers, who were all of Black-African descent (N=190) [ 156 ]. Within Caucasian males (N=22) undergoing treatment for alcohol use disorder, NMR reduced on average 50% from alcohol-detoxification week 1 through the 7 th week of treatment, despite indications that smoking rates had not changed (as indicated by no significant changes in total nicotine equivalents (TNE) in the urine) [ 157 ]. Taken together, these findings suggest that alcohol in e-cigarettes may influence nicotine effects and, if delivered chronically in sufficient levels, may influence nicotine metabolism.…”
Section: E-liquid Components and Characteristicsmentioning
confidence: 99%
“…3 Moreover, studies have shown a higher prevalence of cigarette smoking or drug abuse among subjects who engage in heavy or frequent binge drinking. [3][4][5] AUDs are highly comorbid with mood and anxiety disorders in adults and are associated with substantial societal and personal costs. In a study conducted by Grant et al, among adults seeking treatment for an AUD, 40.69% and 33.3% were diagnosed with at least one current comorbid mood disorder and anxiety disorder, respectively.…”
Section: Introductionmentioning
confidence: 99%